De novo ITPR1 variants are a recurrent cause of early-onset ataxia, acting via loss of channel function. (November 2018) - Synofzik, Matthis; Helbig, Katherine; Harmuth, Florian; Deconinck, Tine; Tanpaiboon, Pranoot; Sun, Bo; Guo, Wenting; Wang, Ruiwu; Palmaer, Erika; Tang, Sha; Schaefer, G.; Gburek-Augustat, Janina; et al.
Abstract We explored the clinico-genetic basis of spinocerebellar ataxia 29 (SCA29) by determining the frequency, phenotype, and functional impact ofITPR1 missense variants associated with early-onset ataxia (EOA). Three hundred thirty one patients from a European EOA target cohort (n = 120), US-American EOA validation cohort (n = 72), and early-onset epileptic encephalopathy (EOEE) control cohort (n = 139) were screened for de novoITPR1 variants. The target cohort was also screened for inheritedITPR1 variants. The variants' functional impact was determined by IP3-induced Ca2+ release in HEK293 cells. 3/120 patients (2.5%) from the target cohort and 4/72 patients (5.5%) from the validation cohort, but none from the EOEE control cohort, carried de novoITPR1 variants. However, mostITPR1 variants (7/10 = 70%) in the target cohort were inherited from a healthy parent, with 3/6 patients carrying disease-causing variants in other genes. This suggests limited or no phenotypic impact of manyITPR1 missense variants, even if ultra-rare and well-conserved. While common bioinformatics tools did not discriminate de novo from otherITPR1 variants, functional characterization demonstrated reduced IP3-induced Ca2+ release for all de novo variants, including the recurrent c.805C>T (p.(R269W)) variant. In sum, these findings show that de novoITPR1 missense variants are a recurrent cause of EOA (SCA29) across independent cohorts, acting via loss of IP3 channel function. InheritedITPR1 variants are also enriched in EOA, but often without strong impact, albeit rare and well-conserved. Functional studies allow identifyingITPR1 variants with large impact, likely disease-causing. Such functional confirmation is warranted for inheritedITPR1 variants before making a SCA29 diagnosis.